2010
DOI: 10.1016/j.ejcts.2009.09.030
|View full text |Cite
|
Sign up to set email alerts
|

Warm versus cold cardioplegia for heart surgery: a meta-analysis

Abstract: Much controversy persists regarding the optimal techniques for myocardial protection during heart surgery. Numerous studies have compared warm cardioplegia with cold cardioplegia for myocardial preservation, but the outcomes were inconclusive. The aim of this meta-analysis of randomised controlled trials (RCTs) was to compare the beneficial and harmful effects of warm and cold cardioplegia during heart surgery. Electronic databases and manual bibliographical searches were conducted. A meta-analysis of all RCTs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
89
0
4

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(98 citation statements)
references
References 40 publications
3
89
0
4
Order By: Relevance
“…Indeed, Buckberg et al demonstrated that electromechanical arrest alone decreases myocardial oxygen requirements by nearly 90%, with only a slight further decrease when lowering myocardial temperature [20]. A recent meta-analysis also demonstrated similar low output syndrome incidence and intra-aortic balloon pump usage with cold and warm cardioplegia [3].…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…Indeed, Buckberg et al demonstrated that electromechanical arrest alone decreases myocardial oxygen requirements by nearly 90%, with only a slight further decrease when lowering myocardial temperature [20]. A recent meta-analysis also demonstrated similar low output syndrome incidence and intra-aortic balloon pump usage with cold and warm cardioplegia [3].…”
Section: Discussionmentioning
confidence: 74%
“…While cold crystalloid cardioplegia ensures myocardial protection by decreasing myocardial oxygen requirements [11], warm blood cardioplegia was considered to improve metabolic and functional recovery of the myocardium [3] and has therefore been adopted by many surgical teams. However, studies such as the Emory Trial failed to demonstrate better myocardial protection with warm cardioplegia and reported significantly higher rates of neurological events in this group [12].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Guru, Jacob and their coworkers (14,15) in two metaanalyses showed that cold blood cardioplegia provides a favorable outcome in terms of lower incidence of low cardiac output syndrome, CK-MB release in comparison with CCC, but the incidence of myocardial infarction and death were similar. In another two meta-analyses Fan, Abah, and their colleagues (16,17) showed no difference between warm and cold cardioplegia on the short-term mortality. Jacquet and Coworkers (18), on 200 patients undergoing coronary artery bypass grafting showed as a better method of myocardial protection the antegrade warm cardioplegia in comparison with combined antegrade and retrograde CCC on the PO cardiac enzymes release, although ischemic arrest duration was significantly shorter in the warm group.…”
Section: Discussionmentioning
confidence: 99%
“…Successful coronary artery bypass grafting (CABG) requires effective myocardial protection and preservation. Although several approaches for myocardial preservation during cardiopulmonary bypass (CPB) have been introduced till now, controversy still exists regarding the best method for this purpose [3][4][5]. The preferred way to protect myocardium is delivering of adequate cardioplegic solution to whole myocardium, and severe occlusion of the coronary arteries limit this delivery by the antegrade route [6].…”
Section: Introductionmentioning
confidence: 99%